How I got my shrunken head - Stine, R. L. (New York : Scholastic, 2009)
Mark is given a shrunken head and brought to the jungle island of Baladora where his aunt has gone missing, and Carolyn, his aunt's assistant explains to Mark that he has "jungle magic," and must help them search for his aunt. Includes survival tips.
"Now with bonus features!"--Cover.
3.7
5-8
Keywords: Head -- Juvenile fiction; Jungles -- Juvenile fiction; Head -- Fiction; Horror stories; Jungles -- Fiction; Head -- Fiction; Horror fiction; Jungles -- Fiction; Horror fiction